PENGEMBANGAN MEDIA PEMBELAJARAN GAMBAR BERSERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS NARASI PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SEKOLAH DASAR - Zuraidah Al Fakhiroh, Zulfa; Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the limitations of the use of learning resources in delivering material and teachers have not developed learning media that can help in learning so that students do not have an interest in writing, find it difficult to compose sentences, and are unable to express ideas and ideas in the form of narrative writing properly and correctly. This research aims to develop a series of picture learning media to improve students' narrative writing skills in Indonesian Language subjects. This research uses the Research and Development (R&D) method using the ADDIE model which consists of five stages, namely analysis, design, development, implementation and evaluation. The results of the study showed that the serial image media was declared "very valid" to be tested, as evidenced by the results of linguist assessment with a percentage of 95.5%, media expert assessment with a percentage of 98%, and material expert assessment with a percentage of 94%. The teacher's response and the student's response to the serialized image media were obtained as a percentage of 96% and 92.5% can be declared "very good" as an Indonesian Language learning medium to improve students' narrative writing skills. Serial image media was declared effective in improving narrative writing skills as evidenced by the results of the assessment of the observation sheet of students' narrative writing skills which obtained a result of 93.75% with the criteria of "very effective".